Consumer Perceptions of Maslahah on Halal-Labeled Madura Herbal Medicine - Mashudi, Mashudi; Dahruji, Dahruji; Ubudiyah, Hakimatul (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
The background of this study is based on the fact that Madura herbal medicine is an interesting alternative treatment and is believed to be effective, as well as being Madurese local wisdom that has been trusted for generations. Therefore, consumers are faced with the choice of the maslahah and halalness of Madura herbal medicine. This study was conducted as part of the description of answers to these problems by testing independent variables using comparative quantitative methods. The research variable was the consumer perceptions of Madura herbal medicine products that were halal-labeled and those that did not have a halal label. The population was consumers of Madura herbal medicine in Kwanyar and Modung districts, Bangkalan Regency. The sampling of the population in this study used Lemeshow's formulation because the exact number of populations was unknown, and the sample determination used a random sampling approach with an accidental sampling technique. The main data collection used questionnaires and documentation techniques. Following the principles of research methodology, a series of data analysis stages have been carried out through questionnaire instrument testing (validity and reliability tests), data distribution normality tests (as a requirement for the t-test), and the one-sample t-test. From the test results, it is known that the perception of the consumer of the maslahah of the Madura herbal medicine is different. Halal-labeled Madura herbal medicine is perceived to guarantee more maslahah, while nonhalal-labeled Madura herbal medicine is not.